Answer:
Can't help on slopes
Step-by-step explanation:
other numbers or graphs have to be included
If you would like to simplify the difference <span>(–7x – 5x^4 + 5) – (–7x^4 – 5 – 9x), you can do this using the following steps:
</span><span>(–7x – 5x^4 + 5) – (–7x^4 – 5 – 9x) = -7x - 5x^4 + 5 + 7x^4 + 5 + 9x = 2x^4 + 2x + 10
The correct result would be </span><span>a. 2x^4 + 2x + 10.</span>
Answer:
First, you change each number to an improper fraction, simplify if possible. Then Multiply the numerators and then denominators, put your answer at lowest terms.
I really hope this helped.!
Answer:
y=4x+1
answer= y=4x
Step-by-step explanation:
y=4x+1
1=4(1)+1
1=5